2014
DOI: 10.1016/j.newast.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and spectrum analysis of Doradus type Kepler target KIC6462033

Abstract: We present results of an asteroseismic study on the γ Dor type Kepler target KIC 6462033. Kepler photometry is used to derive the frequency content and principal modes. High-dispersion ground-based spectroscopy is also carried out in order to determine the atmospheric parameters and projected rotational velocity. From an analysis of the Kepler long cadence time series, we find that the light curve of KIC 6462033 is dominated by three modes with frequencies f 1 =0.92527, f 2 =2.03656 and f 3 =1.42972 d −1 as we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…The largest discrepancy in Table 2 occurs for KIC 6462033 where we find T eff = 18400 K, but Ulusoy et al (2014) find T eff = 7150 K. Our spectrum shows strong He I 4437 and He I 4471 which can only occur in a B star, so the difference is very puzzling. The field is slightly crowded, but KIC 6462033 is by far the brightest star in the field.…”
Section: The Hot γ Dor Starscontrasting
confidence: 54%
“…The largest discrepancy in Table 2 occurs for KIC 6462033 where we find T eff = 18400 K, but Ulusoy et al (2014) find T eff = 7150 K. Our spectrum shows strong He I 4437 and He I 4471 which can only occur in a B star, so the difference is very puzzling. The field is slightly crowded, but KIC 6462033 is by far the brightest star in the field.…”
Section: The Hot γ Dor Starscontrasting
confidence: 54%
“…To reduce the number of false positives, i.e., periodic variability not related to stellar rotation, we discarded 17 eclipsing binaries 2 , 878 planetary candidates 3 , 2 RR Lyrae stars Szabó et al 2010;Benkő et al 2010;Guggenberger et al 2012;Nemec et al 2011Nemec et al , 2013Moskalik et al 2012;Molnár et al 2012), and 84 γ Doradus and δ Scuti stars Ulusoy et al 2014;Balona et al 2011;Uytterhoeven et al 2011;Lampens et al 2013;Balona 2014). In total, 981 stars were discarded, leaving 23 143 targets, which are analyzed as described in the following section.…”
Section: Kepler Datamentioning
confidence: 99%
“…Even when we consider the new theoretical instability strips of β Cep and SPB stars by Moravveji (2016), which were calculated based on the improved opacity tables, KIC 5309849 is still cooler then the red KIC 6462033 shows a rich spectrum of low frequencies. Uytterhoeven et al (2011) reported 46 independent frequencies, whereas Ulusoy et al (2014) identified five independent frequencies and hundreds of combinations and harmonics. Our selection criterion resulted in 509 frequencies.…”
Section: Kic 5309849mentioning
confidence: 99%
“…He I and Mg II lines, do not show clear broadening, which is not fully understood. Ulusoy et al (2014) carried out spectroscopic observations of KIC 6462033. By fitting Hα and Hβ line profiles, they found that the KIC T eff was too high.…”
Section: Identification Of Four B-type Variable Starsmentioning
confidence: 99%
See 1 more Smart Citation